(untitled) (Brazilian Journal of Radiation Sciences, 2021)
The Brazil with the purpose of becoming self-sufficient in the production of radioisotopes and radioactive sources used in nuclear medicine, agriculture and the environment developed the project of a multipurpose reactor of 30 megawatts of power to meet the national demand. In the Energy and nuclear research Institute (IPEN), Nuclear fuel Center (CCN) is responsible for the manufacture of fuel for the reactor IEA-R1 and, possibly, by the multipurpose reactor fuels. In order to meet the demand for the reactors was designed a new manufacturing plant with a maximum capacity of 60 fuel per year, which currently is 10. The increase in production as a consequence will increase the volume of effluents generated. The current concern with the environment it is necessary to draw up a management plan to make the process sustainable, which will result in environmental, economic and social benefits. The fuel production process generates various types of effluent containing uranium or not – being solid, gaseous and liquid with different physical and chemical characteristics. The objective of this work is to follow the process of nuclear fuel production and to identify, quantify and characterize the effluents, especially liquids, to subsequently draw up a management plan and eventually dispose of responsibly in the environment.